Metode Penanaman Karakter Kemandirian Anak Tuna Grahita - Sitwan Sitwan; Marwiah Marwiah (JED (Jurnal Etika Demokrasi), 2020)
Abstract. The problem in this study is how to develop the character of independence for mildly mentally retarded children in SLB Baruga Negeri Kendari City. This study aims to describe the method used by the teacher in planting the character of the gift of mentally disabled children in Baruga SLB in Kendari. This research was conducted at the end of April to the end of May 2015, located at Baruga State Special School (SLB) Kendari City of Southeast Sulawesi Province.This research is descriptive qualitative, which gives a careful description of an individual situation, symptoms, or a particular group. This research will describe the effort to develop the character of independence in children with mild mental disability in SLB Baruga Negeri Kendari City. Data collection instruments are observation sheets and assignment sheets. Data analysis techniques start from data reduction, data coding, and conclusions. This study concludes that the implementation of efforts to develop the character of independence of mildly mentally retarded children in SLB Baruga State of Kendari City has shown good results. This can be seen from the patterns of daily life of mildly mentally retarded children both at school and at home. Children with mild mental retardation have had the independence to maintain cleanliness themselves, maintain the cleanliness of the classroom and school yard. Children with mild disabilities have also been able to independently do light tasks given by teachers at school, complete homework, clean toilets, school grounds and water the plantsKeywords: Mentally Disabled, Character, IndependenceAbstrak.  Masalah dalam penelitian ini adalah bagaimana upaya pengembangan karakter kemandirian bagi anak Mentally Retarded  ringan di SLB Negeri Baruga Kota Kendari. Penelitian ini bertujuan untuk mendeskripsikan metode yang digunakan oleh guru dalam penanaman karakter kemadirian anak Mentally Retarded  pada SLB Baruga di Kendari.  Penelitian ini dilaksanakan pada akhir bulan April sampai dengan akhir bulan Mei 2015, bertempat di Sekolah Luar Biasa (SLB) Negeri Baruga Kota Kendari Provinsi Sulawesi Tenggara. Penelitian ini bersifat deskriptif kuaitatif, yaitu memberikan gambaran secara cermat mengenai suatu keadaan individu, gejala, atau kelompok tertentu. Penelitian ini akan mendeskripsikan upaya pengembangan karakter kemandirian pada anak Mentally Retarded  ringan di SLB Negeri Baruga Kota Kendari. Instrumen pengumpulan data adalah lembar obsevasi dan lembar penugasan. Teknik analisis data dimulai dari reduksi data, koding data, dan simpulan. Penelitian ini meyimpulkan bahwa  pelaksanaan upaya pengembangan karakter kemandirian anak Mentally Retarded  ringan di SLB Negeri Baruga Kota Kendari sudah menunjukkan hasil yang baik. Hal ini dapat dilihat dari pola kehidupan sehari-hari anak Mentally Retarded  ringan baik di sekolah mau pun di rumah. Anak tunag rahita ringan telah memiliki kemandirian untuk menjaga kebersihan dirinya, menjaga kebersihan kelas dan halaman sekolah.  Anak Mentally Retarded  ringan juga sudah mampu secara mandiri mengerjakan tugas-tugas ringan yang diberikan oleh guru di sekolah, menyelesaikan pekerjaan rumah, membersihkan toilet, halaman sekolah serta menyiram tanaman.Kata Kunci: Mentally Retarded , Karakter, Kemandirian